2002
DOI: 10.1172/jci0215614
|View full text |Cite
|
Sign up to set email alerts
|

P311 induces a TGF-β1–independent, nonfibrogenic myofibroblast phenotype

Abstract: P311, also called PTZ17, was identified by suppressive subtraction hybridization as potentially involved in smooth muscle (SM) myogenesis. P311 is an 8-kDa protein with several PEST-like motifs found in neurons and muscle. P311 transfection into two fibroblast cell lines, NIH 3T3 and C3H10 T1/2, induced phenotypic changes consistent with myofibroblast transformation, including upregulation of SM α−actin and SM22, induction of FGF-2, VEGF, PDGF, and PDGF receptors, upregulation of integrins α3 and α5, and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 46 publications
1
32
0
1
Order By: Relevance
“…Thus, these genes represent novel or less well recognized participants in the fibrotic process that were upregulated by PKC-δ. The profibrogenic genes that were downregulated by PKC-δ inhibition ( Figure 4 ), which were confirmed by RT-PCR, included c5orf13, which downregulates TGF-β1 and TGF-βR2 and has been shown to decrease collagen expression and induce differentiation of myofibroblasts to fibroblasts [35]; CXCL6, a chemokine that displays increased expression during progression of liver fibrosis [36]; CXCL12, a chemokine that is a powerful attractant for fibrocytes and that participates in the angiogenesis associated with chronic inflammation and fibrosis and has been found to be increased in pulmonary fibrosis tissues [37][39]; GBP1, an interferon inducible guanylate binding protein that is expressed at gap junctions and is involved in endothelial cell proliferation and invasion [40]; SOX9, which is coexpressed with Col2a1, the gene encoding type II collagen, the major cartilage matrix protein [41] and which has recently been suggested to participate in SSc fibrosis [42]; and TNFRSF19, which is expressed primarily in prostate cells and is capable of activating the JNK pathway and of inducing NFκB activation [43].…”
Section: Discussionmentioning
confidence: 76%
“…Thus, these genes represent novel or less well recognized participants in the fibrotic process that were upregulated by PKC-δ. The profibrogenic genes that were downregulated by PKC-δ inhibition ( Figure 4 ), which were confirmed by RT-PCR, included c5orf13, which downregulates TGF-β1 and TGF-βR2 and has been shown to decrease collagen expression and induce differentiation of myofibroblasts to fibroblasts [35]; CXCL6, a chemokine that displays increased expression during progression of liver fibrosis [36]; CXCL12, a chemokine that is a powerful attractant for fibrocytes and that participates in the angiogenesis associated with chronic inflammation and fibrosis and has been found to be increased in pulmonary fibrosis tissues [37][39]; GBP1, an interferon inducible guanylate binding protein that is expressed at gap junctions and is involved in endothelial cell proliferation and invasion [40]; SOX9, which is coexpressed with Col2a1, the gene encoding type II collagen, the major cartilage matrix protein [41] and which has recently been suggested to participate in SSc fibrosis [42]; and TNFRSF19, which is expressed primarily in prostate cells and is capable of activating the JNK pathway and of inducing NFκB activation [43].…”
Section: Discussionmentioning
confidence: 76%
“…Because myofibroblasts are defined as specialized fibroblasts with smooth muscle-like features, we hypothesized that P311 might also be involved in myofibroblast formation. In fact, our and other studies have shown that P311 can induce primary human fibroblasts [20] and fibroblast cell lines [19, 21] to differentiate into myofibroblasts. We recently found that P311 was highly expressed in EpSCs that are located in the neo-epidermis and hair follicles during wound healing [22] and that P311 promoted EpSC migration.…”
Section: Introductionmentioning
confidence: 81%
“…The high level of expression of P311 in these tissues suggested that it plays an important role in wound healing and scar formation. P311 is a novel gene that encodes an 8-kDa protein which contains several PEST (rich in proline (P), glutamic acid (D), aspartic acid (E), and serine (S) or threonine (T))-like domains and participates in the development of neurons and smooth muscles [19]. Because myofibroblasts are defined as specialized fibroblasts with smooth muscle-like features, we hypothesized that P311 might also be involved in myofibroblast formation.…”
Section: Introductionmentioning
confidence: 99%
“…Double inactivation of LIMS1 and 2 leads to the development of heart failure and fibrosis in mice [11]. NREP regulates the TGF-β signaling pathway, and overexpression of NREP in fibroblasts suffices to induce proliferation and myofibroblastic transformation [12]. NREP is upregulated in hypertrophic skin scars [19], suggesting that this protein may be important for fibrogenesis in vivo.…”
Section: Discussionmentioning
confidence: 99%